Cultural influences on Aesthetic Medicine choices: the role of psychology - Villanueva Tobaldo, Carlota Valeria; Tornero Aguilera, Jose Francisco; Rubio Zarapuz, Alejandro; Clemente Suarez, Vicente Javier (Aesthetic Medicine, 2024)
The intricate relationship between aesthetic medicine and the evolving personal perceptions of beauty, significantly influenced by gender and cultural determinants, has garnered increased academic scrutiny in recent times. In today's digital age, the pervasive influence of social media plays a pivotal role in shaping body image and self-perception, leading to potential psychological disorders. However, when approached with caution and professionalism, aesthetic medicine can transform into a powerful ally, offering considerable psychosocial benefits to the patient. This dual nature underscores the importance of nuanced understanding and ethical considerations in the field of aesthetic medicine. To rigorously scrutinize this interplay, a comprehensive critical review was executed, sourcing information from primary literature, including peer-reviewed scientific journals, and secondary repositories such as bibliographic indices and databases. Systematic searches were performed on platforms like Scopus, Embase, Science Direct, ResearchGate, and the Web of Science using MeSH-aligned keywords: "aesthetic medicine", "sociocultural constructs", "body dysmorphia", "gendered beauty standards", and "cultural aesthetics". To maintain the study's focus and rigor, content that deviated from the core objective, including Ph.D. dissertations, conference papers, and unpublished works, was discarded. Through this meticulous methodology, our review offers an in-depth dissection of how societal standards - predominantly influenced by cultural and gendered paradigms - steer choices towards aesthetic medical procedures. Additionally, it illuminates their ensuing psychological ramifications, with a particular focus on the realm of body dysmorphia. By emphasizing both the therapeutic potential and the possible detrimental psychological effects of aesthetic procedures, this review endeavors to provide valuable insights for medical practitioners, patients, and the broader societal demographic. Ultimately, the analysis underscores the importance of fostering a holistic comprehension of aesthetic decisions, promoting an integrated perspective that encapsulates notions of beauty, self-esteem, and medical ethical considerations.